Cancer-related false knowledge in relatives of cancer patients and the general public - (:unkn) unknown (IMPRIMATUR PUBLICATIONS, 2010)
Purpose: Although there are many myths about cancer in Turkey, there is no study evaluating Turkish public's knowledge about cancer The goals of our research were to: 1) measure the extent of knowledge of cancer among the Turkish public; 2) determine the differences in extent of cancer-related knowledge between participants who have relatives with cancer and those who do not; and 3) determine the sources of knowledge possessed. Methods: Data were obtained from a total of 415 participants (244 female, 171 male), all of them sitting at the Marmara University Faculty of Medicine Hospital (MUFMH) outpatient clinic waiting area for non-cancer-related reasons. Each participant completed a 3-part questionnaire. Appropriate statistical tests were used for comparison. Results: The mean age was 41 years. Of 415 participants, 65.3% stated that they had one or more cancer patient in their immediate family; 70.1% of the participants had a high-school education or greater The questionnaire showed that, depending on the question, anywhere from 1.7% to 88.5% of the general public possesses some false information; furthermore, the difference in accuracy between relatives of cancer patients and non-relatives was marginal. Only 3 specific questions, related to the following ideas, rendered answers that were statistically significantly different between these 2 groups: breast cancer is only seen in females (p < 0.005), cell phones cause cancer (p < 0.001), and cancer is always very painful (p < 0.001). Conclusion: The proportion of false knowledge about cancer was unacceptably high in our cohort. Broader efforts should be made to inform the Turkish public about cancer.
Keywords: cancer; cancer myths; false information; public awareness; Turkey; MYTHS